RUSSIAN INNOVATION BUSINESS: INNOVATION IS A BUZZWORD OR A COMPETITIVE NECESSITY? - N. E. Savvina (Финансы: теория и практика, 2017)
The paper analyzes different points of view on the term «innovative insurance product» and, in particular, points out those features which permit to consider the new product as innovation.The research seeks to substantiate the need to adopt an innovative approach to domestic insurance business as an unalternative condition of its survival on the open global insurance market.The research uses both general scientific method (theoretical modeling) and special methods (such as the descriptive phenomenological method, benchmarking, identification and formulation of the essential qualities or attributes, etc.) The author classifies insurance innovative products in business as follows: commercial (market); technical; financial; organizational and social.The end-to-end life cycle of an innovative insurance product includes all stages of its development: initial stage, project stage and project completion stage). As insurance business is tightly connected to social and economic development of the state, the article reveals main reasons preventing to apply an innovative approach in the insurance sector. Innovation business would be key for Russia to overcome its current stagnation and crisis. The suggested recommendations towards the improvement of cooperation between policyholders and insurers at the innovation product launch step can be used by all interested parties.